Hak Kepemilikan Mahar Berupa Tanah dalam Hukum Perkawinan (Analis Menurut Undang-Undang Pokok-Pokok Agraria) - Supriadi Supriadi (Al-Bayyinah, 2019)
AbstractUU No. 1 of 1974 concerning marriage and Presidential Instruction No. 1 of 1991 concerning the Compilation of Islamic Law (KHI) is one form of unification and codification of the law in Indonesia concerning marriages governing legal consequences including dowry in the form of land. Land law in Indonesia has been based on UU. No. 5 of 1960 concerning Basic Principles of Agrarian Law (UUPA) and Government Regulation No. 24 of 1997 concerning land registration. The issue of dowry in the form of land in the marriage law is inseparable from the provisions of agrarian law. In the principles view of the establishment of "special regulation that excludes general regulations (lex specialis derogat lex generalis)". Therefore, to provide legal guarantees for the ownership of land dowry, registration must be carried out to issue a certificate on behalf of the wife (owner of the dowry).Keywords: Dowry-Land Ownership-Agrarian Law